2019
DOI: 10.1177/0192513x19829501
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Girls’ Disclosure About Dating and Sexuality

Abstract: Adolescents disclose information about romantic relationships and sexuality to family members and friends, but little is known about the correlates of this disclosure. We examined adolescent girls' (N = 68; 34 sister dyads) choice of disclosure partner regarding thoughts/concerns about dating and sexuality. Adolescents were more likely to choose mothers and sisters (compared with friends) as disclosure partners regarding dating and sexuality topics. Using multilevel modeling, we also examined romantic relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…A study in Kenya by Maina, Ushie [ 90 ] revealed similar findings where romantic relationships were covert as they were viewed as immoral as well as disruptive towards achieving education goals. This is a line with a study by Killoren, Campione-Barr [ 91 ] which found that American adolescents would choose to disclose general thoughts and concerns related to sexual relationship to their mothers but would not discuss thoughts and concerns related to dating.…”
Section: Discussionsupporting
confidence: 89%
“…A study in Kenya by Maina, Ushie [ 90 ] revealed similar findings where romantic relationships were covert as they were viewed as immoral as well as disruptive towards achieving education goals. This is a line with a study by Killoren, Campione-Barr [ 91 ] which found that American adolescents would choose to disclose general thoughts and concerns related to sexual relationship to their mothers but would not discuss thoughts and concerns related to dating.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding women’s attraction and influences on partner choice, research has explored the repercussions of social and cultural contexts, such as romantic literature, on the influence on women’s choices and relationship models ( Barros del Río, 2005 ). Beyond the importance of these elements, the influence of social networks and friendship on romantic relationships and partner choice during the start of the relationship and throughout the relationship is clearly crucial ( Wright and Sinclair, 2012 ; Killoren et al, 2019 ; Elboj-Saso et al, 2020 ). Also, research on the language use emphasizes the potential of language in socialization processes ( Burdelski, 2013 ; Rios-González et al, 2018 ; Arnold, 2019 ) and in the transmission of patterns of gender inequalities among children ( da Luz Scherf et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers posit that informal mentoring can serve as a protective mechanism for vulnerable youth (Hurd & Zimmerman, 2010), but studies have yet to examine the role of informal mentors in the lives of youth affected by ADV. However, scholars have considered whether adolescents disclose about ADV (Bundock et al, 2018; Moore et al, 2015) and other forms of victimization (Fernet et al, 2019; Killoren et al, 2019) to individuals (e.g., siblings & teachers) who could potentially fill the role of informal mentor (Hurd & Zimmerman, 2010; Kogan et al, 2011). There is also evidence to support the role of informal mentoring in reducing violence more generally: Culyba et al (2019) found the presence of an informal mentor was negatively associated with violence exposure for adolescent boys.…”
Section: Introductionmentioning
confidence: 99%